The involvement of phosphorylation of myosin phosphatase targeting subunit 1 (MYPT1) and MYPT1 isoform expression in NO/cGMP mediated differential vasoregulation of cerebral arteries compared to systemic arteries - Lubomirov, Lubomir; Schubert, Rudolf (Acta physiologica, 2018)
Aim Constitutive release of NO blunts intrinsic and stimulated contractile activity in cerebral arteries (CA). Here, we explored whether phosphorylation and expression levels of the PKG-sensitive, leucine zipper positive (LZ+) splice variants of the regulatory subunit of myosin phosphatase (MYPT1) are involved and whether its expression is associated with higher cGMP sensitivity. Methods Vascular contractility was investigated by wire myography. Phosphorylation of MYPT1 was determined by Western blotting. Results Constitutive phosphorylation of MYPT1-T696 and T853 was lower and that of S695 and S668 was higher in cerebral arteries from the circulus arteriosus (CA-w) than in femoral arteries (FA), while total MYPT1 expression was not different. In CA-w but not in FA, L-NAME lowered phosphorylation of S695/S668 and increased phosphorylation of T696/T853 and of MLC20-S19, plus basal tone. The increase in basal tone was attenuated in CA-w and basilar arteries (BA) from heterozygous MYPT1-T696A/+ mice. Compared to FA, expression of the LZ+-isoform was 2-fold higher in CA-w coincident with a higher sensitivity to DEA-NONOate, cinaciguat and Y27632 in BA and 8-Br-cGMP (1 μmol/L) in pre-constricted (pCa 6.1) α-toxin permeabilized CAs. In contrast, 6-Bnz-cAMP (10 μmol/L) relaxed BA and FA similarly by 80%. Conclusion Our results indicate that (i) regulation of the intrinsic contractile activity in CA involves phosphorylation of MYPT1 at T696 and S695/S668, (ii) the higher NO/cGMP/PKG sensitivity of CAs can be ascribed to the higher expression level of the LZ+-MYPT1 isoform and (iii) relaxation by cAMP/PKA pathway is less dependent on the expression level of the LZ+ splice variants of MYPT1.
First published: 25 April 2018
Gesehen am 18.07.2019